An efficient privacy solution for electronic health records in cloud computing. (10th March 2021) - Marwan, Mbarek; Sifou, Fatima; AlShahwan, Feda; Temghart, Abdelkarim Ait
Cloud computing is generally seen as the most practical and efficient way to build and deploy electronic medical records (EMR) due to advantages such as scalability and cost savings. However, existing solutions are not mature enough to protect patient data. Besides, traditional security countermeasures should be tailored to achieve the right balance between performance and security. In this respect, we propose a highly secure framework to boost remote image processing. Concretely, we rely on the segmentation method to break up the secret image into small portions; thereby optimising the overall execution time. Additionally, we propose a novel access control based on users' trust and user-managed access (UMA). More interestingly, the trust-aware model can reduce the heavy computational overhead of authorisation decisions in comparison to other checking methods. The implementation results prove the accuracy of this approach to meet the stringent security standards and performance requirements.